The Principal's Administrative Role in Managing Teacher Performance at Madrasah Tsanawiyah Swasta Darul Mahmuda, Hamparan Perak District - Dimas Pratama, Muhamad; Basri, Hasan (Universitas Syiah Kuala, 2025)
The school principal plays a crucial role as the administrator of teacher performance at the Private Tsanawiyah Madrasah Darul Mahmuda in the Hamparan Perak District. This study aims to explore this role and its impact on the quality of education in the madrasah. A qualitative approach with descriptive method was employed, involving observation, in-depth interviews, and documentation as data collection techniques. The research findings indicate that the school principal has responsibilities in various aspects, including the development of training programs, monitoring teacher performance, curriculum development, resource management, professional guidance and development, maintaining discipline and professional ethics, as well as collaboration with external parties. By considering these roles, the school principal can become an effective catalyst for change in enhancing the quality of education at the Private Tsanawiyah Madrasah Darul Mahmuda in the Hamparan Perak District.